Indonesia and United States General System of Preference (US-GSP): Eligibility of Indonesia as a Beneficiary Country - Ismail, Achmad (Global: Jurnal Politik Internasional, 2019)
After 3 years, precisely in 2018, the United States reviewed Indonesia's eligibility in receiving US-General System of Preference (US-GSP) facilities. Interestingly, the results of the review have not yet been published. This happens for the United States assumes that Indonesia implements various trade and investment barriers that have a negative impact on the United States, one of which is due to the policy of limiting imports of horticultural products, the implementation of Gerbang Pembayaran Nasional (GPN) and so on. Then with the current conditions, how about the eligibility of Indonesia if it want to receive GSP facilities. This article argues that Indonesia continues to fulfil the required points as a beneficiary country. Indonesia can also use these points as a source of bargaining power to influence the United States so that the results of the GSP review state that Indonesia is eligible to receive GSP facilities, as well as refuse previous US assumptions. This article uses qualitative research methods with a case study approach with primary (interview) and secondary (literature) data collection techniques. This article concludes that Indonesia is still eligible to receive the GSP facility because Indonesia is trying to fulfil the required points as a source of Indonesia's bargaining power towards the United States.